Niestabilność konstytucyjna jako instrument stabilizacji rządu. Przypadek Kirgistanu (Świat Idei i Polityki, 2007)
The article analyses the issues connected with the creation and functioning of the constitution in post-communist Kyrgyzstan. Ostentatious law and order, repeatedly declared devotion to the principle of 'superiority of the constitution' and ritual references to the constitution concealed legal manipulations and procedures violating the principles, the objective of which was to strengthen the presidential power centre. The structure of the article is supported on the dichotomy: stability - destabilization. In the Kyrgyz context, legal instability was closely interrelated with stabilization of the dominant presidential power. The text specifies the factors responsible for the legal destabilization of the political system, reflected in multiplication of law, lack of hierarchy of legal acts, multiple changes of the constitution frequently made with violation of the principles. Especially the significance of the president's ambition aiming at unlimited power is exhibited. This article shows the dynamics of the law creation process shaped by tensions between the president and the parliament. It also indicates other factors connected with the political culture, the lack of democratic political elites, the low legal culture level, and the impingement of the Soviet heritage.